PROSPECTS FOR THE DEVELOPMENT OF GREEN HOTEL BUSINESS IN MODERN REALITIES (Development Service Industry Management, 2025)
The article examines the relevance and prospects for the development of greening of enterprises in the hotel industry of Ukraine as an important area of innovation in the context of sustainable development of the tourism industry.The article is aimed at studying the current trends and prospects of greening the enterprises of the hotel industry in Ukraine, as well as identifying the key areas for the introduction of ‘green’ technologies in the activities of accommodation facilities in the context of ensuring sustainable development of the tourism industry.The author emphasises the main factors that determine the implementation of environmental initiatives in the hotel business, in particular: the perception of owners and managers, government regulation, consumer support and economic benefits for enterprises. The article also focuses on the importance of environmental certification of accommodation facilities for increasing the competitiveness of hotel companies and meeting the growing demand for environmentally responsible accommodation services.The importance of eco-design as one of the key criteria of a green hotel, which directly affects the optimisation of resource use and reduction of negative impact on human health, is emphasised. The author discusses the obstacles and opportunities for implementing sustainability standards in the hotel industry, including the financial constraints of small and medium-sized hotels compared to chain hotels, and the position of customers who are focused on comfort and price rather than environmental friendliness. The author also emphasises the impact of martial law in the country as a fundamental barrier to the transition to green hospitality, which forces business owners to focus on restoring facilities rather than investing in environmental initiatives.
Keywords: ecodesign; green hotel; environmental barriers; hotel industry; greening; green technologies; sustainable development; certification